Analysis of the stress distribution in non-splinted mandibular anterior teeth and teeth splinted by universal periodontal splint using finite element method - Bida, V.; Guryn, P.; Viun, G. (Actual Dentistry, 2018)
Background. Numerical calculated of the stresses in the dentition system by the finite elements method software is topically issue in dentistry. Finite element analysis can explore mechanism of the stress distribution and substantiate necessity to splinted teeth. In return, the reduction of the load on the remaining, but damaged by periodontitis, periodontal tissues can support long-term remission. Purpouse: to analyze the stress distribution and identify the areas of the max von Mises stress in non-splinted mandibular anterior teeth and teeth splinted by universal periodontal splint. Methods. In the study was used the ANSYS Workbench 17.0 finite elements method software to analyze the three dimensional finite element model of a system «abutment teeth-periodontal tissues-bone» with force of 100 and 200 N. Three dimensional finite element model of a mandibular anterior teeth were designed, which included 8 teeth (incisors, canines, and first premolars) with different loss of bone support (50 and 75 %). Model of universal folding periodontal splint were established for comparison. The models were designed in the «Solid Works 2006». Result. The stress in the model of 50 % bone loss and force of 100N was unevenly distributed. Max von Mises stress in periodontal tissues and bone was 21,77 and 33,82 MPa, accordingly. In case of using model of 75 % bone loss equivalent von Mises stress was increased to 65.82 MPa (vestibular surface incisors) and to 88,50 MPa (bone). Using universal folding periodontal splint was decreased numerical findings to 7.0 and 6.03 MPa von Mises stress in the periodontal tissues and bone, accordingly in model with 50 % bone loss, and 13.3 and 36.12 MPa stress in model with 75 % bone loss. Conclusions. Significant unevenly stress in periodontal tissues with different level of bone loss is pathological and reinforce periodontitis course due to disturbance in the blood supply and accelerate development pathologic teeth migration. Using universal folding periodontal splint alloys distribution the bite forces more physiologically and decrease stress in supporting tissues about three times. Key words: periodontitis, periodontal splints, splinting, finite elements method.